A simple and efficient method for extracting S. Rolfsii DNA for PCR based diversity studies - Ssekamate, Allan Male; Kato, Fred; Mukankusi, Clare (OMICS Publishing Group, 2018)
Present methods of extracting DNA from Sclerotium rolfsii use a lot of hazardous organic chemicals to extract high quality DNA. Extraction of the DNA is further complicated by exopolysaccharides that bind to the DNA making it mucilaginous. We developed a simple and efficient protocol for extracting DNA high quality from S. rolfsii. Our method uses a DNA extraction buffer that contains sodium dodecyl sulphate and proteinase K to inactivate proteins and high salt concentration to precipitate the exopolysaccharides. It uses neither phenol, chloroform nor isoamyl alcohol during the DNA extraction process. It also does not require freeze drying of the mycelia and grinding in liquid nitrogen. Using our method, a sufficient amount of pure (mean A260: A280=1.91 ± 0.001) DNA (mean = 55.57 ± 0.002 ng/µl) was obtained from 100 mg of mycelia. The DNA was amenable to PCR amplification using inter-simple sequence repeat primers and primers targeting the internal transcribed spacer region of S. rolfsii. Our method will be very useful in laboratories that don’t have access to liquid nitrogen and freeze-drying facilities and will be a catalyst for PCR-based phylogenetic studies of this important pathogen of common bean.